Adjustments in motor unit properties during fatiguing contractions after training - Vila-Chã, Carolina (2014)
The objective of the study was to investigate the effect of strength and endurance training on muscle fiber membrane properties and discharge rates of low-threshold motor units of the vasti muscles during fatiguing contractions. Methods: Twenty-five sedentary healthy men (age (mean T SD) = 26.3 T 3.9 yr) were randomly assigned to one of three groups: strength training, endurance training, or a control group. Conventional endurance and strength training was performed 3 dIwkj1, during a period of 6 wk. Motor unit conduction velocity and EMG amplitude of the vastus medialis obliquus and lateralis muscles and biceps femoris were measured during sustained isometric knee extensions at 10% and 30% of the maximum voluntary contraction before and immediately after training. Results: After 6 wk of training, the reduction in motor unit conduction velocity during the sustained contractions at 30% of the maximum voluntary force occurred at slower rates compared with baseline (P G 0.05). However, the rate of decrease was lower after endurance training compared with strength training (P G 0.01). For all groups, motor unit discharge rates declined during the sustained contraction (P G 0.001), and their trend was not altered by training. In addition, the biceps femoris–vasti coactivation ratio declined after the endurance training. Conclusions: Short-term strength and endurance training induces alterations of the electrophysiological membrane properties of the muscle fiber. In particular, endurance training lowers the rate of decline of motor unit conduction velocity during sustained contractions more than strength training